Dimensional analysis in the growth kinetics of FeB and Fe2B layers during the boriding process. (2nd April 2007) - Torres, R.; Campos, I.; Ramirez, G.; Bautista, O.; , J. Martinez
Dimensional analysis is presented as a powerful tool in the study of the paste boriding process. In particular, a dimensional method is used to study the growth kinetics of the boride layers FeB and Fe2 B. Experiments were performed in AISI 1045 steel and AISI M2 steel, to test the suggested model. Results indicate that the growth of boride layers obeys power laws of the form γ = αχ β, where the α and β constants are a function of the material and the interface of interest.